2021
DOI: 10.1155/2021/9927864
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin Protects Small Intestine from Lipopolysaccharide‐Induced Mitochondrial Dysfunction via Activating Mitochondrial Antioxidant Systems and Mitochondrial Biogenesis in Broiler Chickens

Abstract: Bisdemethoxycurcumin is one of the three curcuminoids of turmeric and exhibits good antioxidant activity in animal models. This study is aimed at investigating the effect of bisdemethoxycurcumin on small intestinal mitochondrial dysfunction in lipopolysaccharide- (LPS-) treated broilers, especially on the mitochondrial thioredoxin 2 system and mitochondrial biogenesis. A total of 320 broiler chickens were randomly assigned into four experimental diets using a 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Our results showed that oxidative phosphorylation complexes downregulated the genes and reduced the mitochondrial oxidative phosphorylation activity in jejunum tissue, resulting in impaired mitochondrial function by E. coli infection. This was similar to the report that showed that the activities of jejunal mitochondrial respiratory complexes and the level of ATP were reduced after intestinal damage ( Zhang et al., 2021 ). The mechanism was also demonstrated at the cellular level: LPS-activated macrophages are characterized by high glycolysis and low oxidative phosphorylation ( Vats et al., 2006 ; Rodríguez-Prados et al., 2010 ), and as a key component of macrophage polarization, these changes contribute to a kind of tissue self-repair in inflammation ( Ip et al., 2017 ; Carrasco-Pozo et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that oxidative phosphorylation complexes downregulated the genes and reduced the mitochondrial oxidative phosphorylation activity in jejunum tissue, resulting in impaired mitochondrial function by E. coli infection. This was similar to the report that showed that the activities of jejunal mitochondrial respiratory complexes and the level of ATP were reduced after intestinal damage ( Zhang et al., 2021 ). The mechanism was also demonstrated at the cellular level: LPS-activated macrophages are characterized by high glycolysis and low oxidative phosphorylation ( Vats et al., 2006 ; Rodríguez-Prados et al., 2010 ), and as a key component of macrophage polarization, these changes contribute to a kind of tissue self-repair in inflammation ( Ip et al., 2017 ; Carrasco-Pozo et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Bisdemethoxycurcumin, luteolin, quercetin, flavone, and beta-ecdysone were the top five active ingredients ranked by degree according to the component-target-disease network, which were potentially the main active ingredients in the treatment of pancreatic cancer. Bisdemethoxycurcumin is reported with antifibrosis, antiapoptosis, antioxidant, and anti-inflammatory characteristic in various diseases [44][45][46]. Bisdemethoxycurcumin is also reported with antitumor effects in hepatocellular carcinoma, breast cancer, and non-small-cell lung cancer [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to its instability and low water solubility, curcumin presents a low oral bioavailability, resulting in limited therapeutic applications [28]. Besides curcumin, demethoxycurcumin and BDMC have also exhibited excellent beneficial pharmacological actions, including anti-oxidant, anti-inflammatory, neuroprotective, antihypertensive, and more [29][30][31]. Compared with curcumin and demethoxycurcumin, BDMC is more stable in physiology, indicating that BDMC may have more therapeutic applications [32,33].…”
Section: Discussionmentioning
confidence: 99%